Decolonising management and organisational knowledge (MOK): Praxistical theorising for potential worlds. (September 2021) - Jammulamadaka, Nimruji; Faria, Alex; Jack, Gavin; Ruggunan, Shaun
This special issue (SI) editorial contributes to ongoing efforts worldwide to decolonise management and organisational knowledge (MOK). A robust pluriversal discussion on the how and why of decolonisation is vital. Yet to date, most business and management schools are on the periphery of debates about decolonising higher education, even as Business Schools in diverse locations function as contested sites of neocolonialism and expansion of Western neoliberal perspectives. This editorial and special issue is the outcome of a unique set of relationships and processes that saw Organization host its first paper development workshop in Africa in 2019. This editorial speaks to a radical ontological plurality that up-ends the classical division between theory and praxis. It advocates praxistical theorising that moves beyond this binary and embraces decolonising knowledge by moving into the realm of affect and embodied, other-oriented reflexive, communicative praxis. It underscores the simultaneous, contested and unfinished decolonising-recolonising doubleness of praxis and the potential of borderlands locations to work with these dynamics. This special issue brings together a set of papers which advance different decolonising projects and grapple with the nuances of what it means to 'do' decolonising in a diversity of empirical and epistemic settings.